Virtual Autopsy and Digitalization of Medico-legal Records: A Need in Covid Era - Dutta , A; Saini , V (Journal of Indian Academy of Forensic Medicine, 2023)
Post-mortems are done as a tool in proceedings of medico-legal cases. Autopsy exposes the forensic medical practitioners to body cavities, underlying organs and biological fluids that may be major sources of contamination, especially during the pandemic era. Since death tolls have been higher during these times, to prevent spread of viral infections, post-mortem services had been completely halted. Virtual autopsy examinations were then considered by Forensic Medical experts throughout the world during the Covid outbreak and stands as an important future tool in the post-covid era too. Also, documents pertaining to medico-legal examination needs to be handled with integrity and ethics, which prompts its digitalization. This paper aims to study the risks encountered by forensic medical practitioners while conducting death investigations, techniques of virtual autopsy, its legal admissibility, online portals for maintaining reports, their current scenario and future prospects.